A Strategy for Improving the Quality of Ghost Imaging. (9th April 2020) - Liu, Xin; Bo, Su; Ye, Zhiyuan; Qiu, Panghe; Ding, Jing
Abstract : A new method is proposed to improve the signal-to-noise ratio (SNR) of regions of interest (ROIs) in a ghost imaging (GI) system with uneven speckle illumination. The imaging results in a GI system can be distorted when there is an uneven distribution of light. In this study, three thin-film polarizers are used to create illumination patterns in uneven light intensity distribution. In particular, the polarizer set is loaded on the object arm only, that is, the original uniformly distributed light field is still acquired by the reference arm. This small change in the light path eliminates the distortion caused by uneven illumination while increasing the SNR of the ROI. This strategy has been confirmed in principle and through simulation and experiments.